Developing an intelligent system to acquire meeting knowledge in problem-based learning environments - Chiang, A.; Baba, M.S. (2006)
MALESAbrain1-3 is an intelligent algorithm which originally is designed for problem-based learning (PBL) environment. Similarly, the algorithm proposed in MALESAbrain can, be used to deal, the problem of conducting a meeting among learners to solve problems. This project adapts the original MALESAbrain definitions and algorithm to create an intelligent learning tool; then, testing the tool in a students' meeting to discuss "To build up programming skills for computer science students, do you agree JAVA is a proper language in the first year foundation, course for computer science students"? Consequently; this paper concludes that MALESAbrain is a new methodology for meeting, which (1) reduces the unnecessary human intervention and (2) changes a meeting atmosphere from debate to problem-based learning for the knowledge acquisition.